Dampak Perkembangan Teknologi dalam Pendidikan - Tamaulina Br. Sembiring; Ghosy Thosan; Muhammad Fadli; Rudi Apriyanto; Stella Namira; Thania Dhea Fany Purba (PT PUSTAKA CENDEKIA GROUP, 2024)
Rapid technological changes have had a significant impact on the world of education, both positive and negative. Technology makes it easier to access information, supports distance learning, and creates more interactive and interesting learning methods in the world of education. In addition, technology also encourages the advancement of students' and teachers' digital skills, which is very important in the era of digitalization. However, there are also challenges such as dependence on technology, digital distractions, access gaps, and health impacts due to excessive use of digital devices. This research uses a literature study method to identify the positive and negative impacts of technology in education as well as solutions that can be implemented. The results of the analysis show that digital literacy, supervision and equitable access to technology are the keys to optimal use of technology. With proper management, technology can be an effective tool for improving the quality of education.